The Effectiveness of Media-Based Mind Mapping in Teaching Short Story Writing at SMP Unismuh Makassar - Ulviani, Maria; Amin, Sulvahrul; Hafid, Hilda; Kemala, Rosmalina (Edumedia Solution, 2025)
This article discusses a community engagement project aimed at enhancing short story writing skills through media-based mind mapping at SMP Unismuh Makassar. The school faced challenges in improving students' creative writing abilities, particularly in narrative construction. In response, a mind mapping technique using media was implemented as an innovative teaching method. The project involved interactive workshops where students were guided in using mind mapping to organize their ideas and develop structured narratives. The results revealed a significant improvement in students' ability to create coherent and creative short stories. Feedback from both students and teachers indicated that the method effectively boosted student engagement and writing quality. The study concludes that media-based mind mapping is an effective tool for improving short story writing in educational settings, fostering creativity, and enhancing writing competencies.